Risk factors for retrovirus and hepatitis virus infections in accepted blood donors. Issue 5 (4th December 2014) - Custer, Brian; Kessler, Debra; Vahidnia, Farnaz; Leparc, German; Krysztof, David E.; Shaz, Beth; Kamel, Hany; Glynn, Simone; Dodd, Roger Y.; Stramer, Susan L.; NHLBI Retrovirus Epidemiology Donor Study‐II (REDS‐II)
<x xml:space="preserve">Abstract</x> Background Risk factor surveillance among infected blood donors provides information on the effectiveness of eligibility assessment and is critical for reducing risk of transfusion‐transmitted infection. Study Design and Methods American Red Cross, Blood Systems, Inc., New York Blood Center, and OneBlood participated in a case‐control study from 2010 to 2013. Donors with serologic and nucleic acid testing (NAT) or NAT‐only confirmed human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV), or serology‐confirmed human T‐lymphotropic virus (HTLV) infections (cases) and donors with false‐positive results (controls) were interviewed for putative behavioral and demographic risks. Frequencies and adjusted odds ratios (AORs) from multivariable logistic regression analyses for each exposure in cases compared to controls are reported. Results In the study, 196 HIV, 292 HBV, 316 HCV, and 198 HTLV cases, and 1587 controls were interviewed. For HIV, sex with an HIV+ person (AOR, 132; 95% confidence interval [CI], 27‐650) and male‐male sex (AOR, 62; 95% CI, 27‐140) were primary risk factors. For HBV, first‐time donor status (AOR, 16; 95% CI, 10‐27), sex with an injection drug user (IDU; AOR, 11; 95% CI, 5‐28), and black race (AOR, 11; 95% CI, 6‐19) were primary. For HCV, IDU (AOR, 42; 95% CI, 13‐136), first time (AOR, 18; 95% CI, 10‐30), and a family member with hepatitis (AOR, 15; 95% CI, 6‐40) were primary. For HTLV, sex with an IDU (AOR, 22; 95% CI, 10‐48), 55 years old or more (AOR, 21; 95% CI, 8‐52], and first time (AOR, 15; 95% CI, 9‐24) were primary. Conclusions Despite education efforts and risk screening, individuals with deferrable risks still donate; they may fail to understand or ignore or do not believe they have risk. Recipients have potential transfusion‐transmitted infection risk because of nondisclosure by donors.